Demonstration of InGaN full-color monolithic micro-LED display using stacking and selective removal of the light-emitting layer - Koichi Goshonoo; Koji Okuno; Masaki Ohya (Applied Physics Express)
A full-color monolithic micro-light-emitting diode (LED) display based on InGaN quantum wells is demonstrated. We stacked red, green, and blue (RGB) light-emitting layers and selectively removed and regrew a p-type layer to create distinct areas on a single chip that emitted RGB colors. Subsequently, we fabricated a full-color monolithic micro-LED chip with a pixel pitch of 30 μm and pixel number of 96 × 96. Each color subpixel emits light with a single peak. We obtained a full-color image by driving the chip using a microcontroller. The proposed semiconductor process-based method enables the fabrication of low-cost and high-resolution microdisplays.